Impact of absence of subjective memory complaints on characteristics of meaningful occupations in community-dwelling older people - Katsushi Yokoi; Nobuyuki Miyai; Yukiko Sougawa; Sonomi Hattori; Miyoko Utsumi; Megumi Nakamura; Mikio Arita (Archives of Gerontology and Geriatrics Plus)
Background: Subjective memory complaints increase with age, leading to limitations in daily life. Subjective memory complaints should be considered from the perspective of occupations closely related to daily life. This study investigated the association between the absence of subjective memory complaints and characteristics of meaningful occupations. In this study, occupation is defined not only as work but, more broadly, as important activities individuals perform. Study design: A community-based cross-sectional study. Methods: This study included 259 community-dwelling older people (aged 73.9 ± 5.8 years, 100 males and 159 females) with Mini-Mental State Examination-Japanese scores ≥25. Subjective memory complaints were assessed using a question from the Centers for Disease Control and Prevention. Questionnaires on meaningful occupations (number, frequency, continuation, performance, and satisfaction) were administered. Logistic regression analysis was performed to examine the association between the absence of subjective memory complaints and occupational characteristics, adjusting for age, education, body mass index, alcohol consumption, smoking status, and disease status as covariates. Results: Of the 259 participants, 131 (50.6 %) had no subjective memory complaints. Occupational performance was associated with the absence of subjective memory complaints, with an adjusted odds ratio of 1.53 (95 %CI = 0.99–2.36) for males. Occupational satisfaction was significantly associated with the absence of subjective memory complaints, with an adjusted odds ratio of 1.39 (95 %CI = 1.02–1.90) for females. Conclusion: The absence of SMCs appears to be associated with positive subjective occupational performance and satisfaction; however, further research, including an exploration of gender differences and potential associations, is needed.